Characterization of morphology and potential of pineapple genetic resources in peatland of Jambi Province - Desi Hernita; Eva Salvia; Julistia Bobihoe (Indonesian Society for Horticulture (Perhimpunan Hortikultura Indonesia Komisariat Aceh), 2019)
Jambi Province has large peatlands (621,089 ha). Utilization of that land in agricultural sector will contribute in economic development of surrounding society. Tangkit and Paun Pineapple are plant genetic resource (PGR) that must be maintained and secured from extinction and erosion of genetic potential. This is because the real PGR continues to be utilized for the survival and welfare of the community. The research purpose was to know the morphological of PGR pineapple that have potential to grow, produce and adapt in peatland of Jambi Province. Survey method was used in this research and conducted in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency and Sungai Baung Village, Pengabuan District of Tanjung Jabung Barat Regency, Jambi Province in 2016 and 2017. The results showed that significant different were occurred between Tangkit and Paun pineapple in leaf morphology, flowers, fruit, harvesting age and production/ha. Production of Tangkit and Paun pineapple were 13.5 ton/ha and 9.1 - 13 ton/ha respectively. The leaves of Tangkit pineapple were prickly, meanwhile, Paun pineapple was not thorny; Fruit of Tangkit pineapple was round oval, and Paun pineapple cones-like with 3-4 times bigger in size than Tangkit pineapple (3.5 - 5 kg). Paun Pineapple can only grow in peatland with 3 m depth while on shallow peat fruit production is not optimal. Tangkit Pineapple grow and produce well on peatland with pH ≤ 5.0. Paun Pineapple also well adapted to low peatlands with elevation 0 - 30 m asl and soil pH 4.5 - 6.5.